Towards naturalistic scanning environments for wearable magnetoencephalography - Rea, Molly (2023)
Magnetoencephalography (MEG) is a neuroimaging technique that probes human brain function, by measuring the magnetic fields generated at the scalp by current flow in assemblies of neurons. A direct measure of neural activity, MEG offers high spatiotemporal resolution, but limitations imposed by superconducting sensor technologies impede its clinical utility. Specifically, neuromagnetic fields are up to a billion times smaller than that of the Earth, meaning MEG must be performed inside a magnetically shielded room (MSR), which is typically expensive, heavy, and difficult to site. Furthermore, current MEG systems employ superconducting quantum interference devices (SQUIDs) to detect these tiny magnetic fields, however, these sensors require cryogenic cooling with liquid helium. Consequently, scanners are bulky, expensive, and the SQUIDs must be arranged in a fixed, one-size-fits-all array. Any movement relative to the fixed sensors impacts data quality, meaning participant movement in MEG is severely restricted. The development of technology to enable a wearable MEG system allowing free participant movement would generate a step change for the field.